The Role of Family Medicine Training in Addressing Workforce Challenges in Rural Liberia – Early Implementation Experience. Issue 1 (8th October 2021) - Sanoe, Ibrahim; Beyan-Davies, Kolu; Anyango, Sarah; Ekwen, Gerald; Pierre, Jacquelin; Farley, Jessica; George, Methodius; Marsh, Regan H.; Luma, Maxo; Okiror, David; Sacra, Richard; Cook, Rebecca
Background: Liberia has a severe shortage in the health workforce, which is amplified in rural areas. Many talented Liberians leave the country for post-graduate education; those physicians who do stay are concentrated in Monrovia. Objective: We initiated a family medicine specialty training program (FMSTP) to increase the number of well-trained physicians who have the knowledge, skills, and commitment to meet the health needs of the Liberian people. Methods: The Liberian College of Physicians and Surgeons (LCPS) family medicine program is a three-year post-graduate course that follows the West African College of Physician (WACP) curriculum. The program has a longitudinal rural training component supported by Partners in Health in Maryland county, where residents gain experience in a remote and under-served region. The program is evaluated through resident evaluations and ultimately bench-marked by accreditation and exam pass rates. Findings: The FMSTP commenced in July 2017, and the first rural rotation was in January 2018. To-date 13 residents have completed a total of 43 rotations in Maryland. Residents surveyed highly rated the faculty and their rural rotations. They identify more hands-on involvement in patient care, exposure to community health, and one-on-one time with faculty as the greatest assets of the rural training experience. Accreditation from the WACP was granted in December 2018. One of the graduating residents from the first class in 2020 is now serving as the first Liberian family medicine specialist in Maryland County. Discussion: Investing in a strong rural training component in our FMSTP has not only strengthened the program but has also built the infrastructure to establish our rural site as an attractive teaching hospital for intern doctors and nursing students. As the program continues to grow, success will be measured by the proportion of Liberian medical students entering the family medicine training program, retention of family medicine physicians in rural areas, and ultimately progress towards universal health coverage (UHC).